Exciton-enhanced recombination in silicon at high concentrations of charge carriers - Sachenko, A.V.; Gorban, A.P.; Kostylyov, V.P. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2000)
The interrelation between processes of electron-hole recombination and annihilation of excitons in silicon is examined. It is shown, that recombination processes can be essentially influenced by the exciton annihilation at high concentrations of non-equilibrium or equilibrium charge carriers. In n-type material a correlation between Shockley-Reed-Hall lifetime values and a square-law recombination coefficient is found. This correlation is explained in terms of assumption that both Shockley-Reed-Hall lifetime, and non-radiative exciton annihilation time constant responsible for a square-law recombination, are determined by the same deep level. It is stated, that the mentioned regularities should essentially affect the bulk lifetime values in n-type silicon at doping concentration exceeding 10¹⁶ cm⁻³.